NGHIÊN CỨU ĐỘNG HỌC QUÁ TRÌNH NITRAT HÓA SỬ DỤNG KĨ THUẬT VI SINH TẦNG CHUYỂN ĐỘNG TRONG MÔI TRƯỜNG NƯỚC MẶN - Cat, Lê Văn; Hồng Đức, Phạm Thị (Vietnam Journal of Science and Technology, 2012)
SUMMARY Nitriﬁcation by moving bed biofilm reactor (MBBR) involves physical, chemical and biological processes, that are governed by a variety of parameters such as substrate and dissolved oxygen concentrations, organic matters, temperature, pH, alkalinity, salinity and turbulence level. The impacts of these parameters upon nitriﬁcation kinetics make predicting the performance of a bioﬁlter for a give application an engineering challenge. Knowing the performance of a bioﬁlter is critical for both designers and managers. This paper presents the current knowledge the nitriﬁcation kinetics are affected by salinity and initial concentration. In this study, the kinetical data of nitrification process conducted by MBBR under oligotrophic condition and in saline medium were analysed by the general kinetics model of n - th order equation and compaired with other data analysis procedures. The established procedure was used to investigate the influence salinity on the kinetical behaviours of the nitrification process under oligotrophic conditions in saline water. Low ammonium concentration (oligotrophic) and high salinity within a system represent the inhibitory factors on the process, which considerably reduce the nitrification performances. The general kinetics model of n - th order equation could be use to simulate kinetical nitrification in circumstance conditions.